PENEGAKAN HUKUM PIDANA MILITER TERHADAP PRAJURIT TNI YANG MELAKUKAN TINDAK PIDANA THTI (KETIDAKHADIRAN TANPA IJIN) DI PENGADILAN MILITER I02 MEDAN - Silalahi, Joel; Esther, July (JURNAL AKTA YUDISIA, 2024)
This research discusses the crime of unauthorized absence (THTI) within the Indonesian National Armed Forces (TNI), focusing on 40 cases that occurred at the Military Court I-02 Medan between 2021 and 2024. The purpose of this research is to identify the factors underlying the occurrence of unauthorized absence (THTI) and the methods used by law enforcement to prove such violations. The method used is normative legal research, which includes in-depth interviews with Lieutenant Colonel Ziky Suryadi, S.H., MH., a judge at the court, as well as a literature review from various legal sources. The research results show that the main factors causing TNI soldiers to commit THTI include financial pressure due to debts, involvement in gambling, domestic disputes, and dissatisfaction with their military careers. Additionally, some soldiers engaged in illegal activities to earn extra income, which led to the decision to be absent without leave as a form of escape from the problems they faced. Law enforcement proved these violations through investigation procedures and evidence collection in accordance with military law provisions. The conclusion of this study emphasizes the importance of a deep understanding of the factors causing THTI and the need for more effective prevention and handling efforts to maintain discipline among TNI soldiers, in order to improve the performance and image of the military institution as a whole.Keywords: Law enforcement, Military criminal Law, THTI (absent without leave)